Reassembling the Centaurea tenorei group (Asteraceae) puzzle: typification of the names - Santangelo, Annalisa; Del Guacchio, Emanuele; Cennamo, Paola; Caputo, Paolo (Phytotaxa, 2017)
The Centaurea tenorei group (Asteraceae), strictly endemic to the Peninsula of Sorrento (southern Italy), has been recently split into three microspecies: C. tenorei s.str., C. montaltensis and C. lacaitae. Seven pertinent names are typified in this work and preliminarily identified according to the three species concept. The selected types clearly reflect the variability of the group and some names may correspond to hybrids with other Centaurea or to intermediates between the three microspecies, which appear therefore hard to discriminate on morphological grounds.